Profesionalisme dan Kepemimpinan dalam Meningkatkan Kinerja Auditor: Peran Pelatihan sebagai Pemoderasi - Devila Chikita Yumna; Ceacilia Srimindarti (Universitas Muhammadiyah Metro, 2026)
This study aims to examine the effect of professionalism and leadership style on auditor performance, with auditor training as a moderating variable. This research was conducted at a Kantor Akuntan Publik in Semarang City that is registered with the Institut Akuntan Publik Indonesia (IAPI). The sampling technique uses convenience sampling. A total of 84 auditors became respondents using the survey method. The data analysis technique uses Moderated Regression Analysis (MRA). The results of the study show that professionalism has a significant positive effect on auditor performance. Leadership style has no effect on auditor performance. Auditor training cannot moderate the influence of professionalism and leadership style on auditor performance